Research advances in Apert syndrome - Satrupa Das; Anjana Munshi (Elsevier, 2018)
Apert syndrome is one of the several genetic syndromes associated with craniosynostosis, a condition that includes premature fusion of one or multiple cranial sutures. There has been significant clinical variation among different sutural synostoses and also within particular suture synostosis. Enormous progress has been made in identifying various mutations associated with Apert Syndrome. Although a causal gene has been defined, the precise role of this mutation in producing craniofacial dysmorphology and other related abnormalities is in the process of discovery. Most of the understanding regarding this rare disorder has been possible due to mouse models that have helped in deciphering the elements of this rare human disease. Thus, molecular and cellular understanding of the disease has taken a leap and further with the advent of technology definitive diagnosis of the syndrome is no more of an issue. In this review, we have discussed and consolidated the possible molecular studies that have contributed in understanding of this rare syndrome. This article may help clinicians and researchers to inform about the latest progress in Apert syndrome.